Left Ventricular Myocardial Function in Children With Pulmonary Hypertension: Relation to Right Ventricular Performance and Hemodynamics - Burkett, Dale A. (Circ Cardiovasc Imaging, 2015)
BACKGROUND: Through ventricular interdependence, pulmonary hypertension (PH) induces left ventricular (LV) dysfunction. We hypothesized that LV strain/strain rate, surrogate measures of myocardial contractility, are reduced in pediatric PH and relate to invasive hemodynamics, right ventricular (RV) strain, and functional measures of PH. METHODS AND RESULTS: At two institutions, echocardiography was prospectively performed in 54 pediatric PH patients during cardiac catheterization, and in 54 matched controls. PH patients had reduced LV global longitudinal strain (LS) (-18.8 [-17.3 - -20.4]% vs. -20.2 [-19.0 - -20.9]%, P=0.0046) predominantly due to reduced basal (-12.9 [-10.8 - -16.3]% vs. -17.9 [-14.5 - -20.7]%, P<0.0001) and mid (-17.5 [-15.5 - -19.0]% vs. -21.1 [-19.1 - -23.0]%, P<0.0001) septal strain. Basal global circumferential strain (CS) was reduced (-18.7 [-15.7 - -22.1]% vs. -20.6 [-19.0 - -22.5]%, P=0.0098), as were septal and free-wall segments. Mid CS was reduced within the free-wall. Strain rates were reduced in similar patterns. “Basal septum” LS, the combined average LS of basal and mid interventricular septal segments, correlated strongly with degree of PH (r=0.66, P<0.0001), pulmonary vascular resistance (r=0.60, P<0.0001), and RV free-wall LS (r=0.64, P<0.0001). Brain natriuretic peptide levels correlated moderately with septal LS (r=0.48, P=0.0038). PH functional class correlated moderately with LV free-wall LS (r=-0.48, P=0.0051). The septum, shared between ventricles and affected by septal shift, was the most affected LV region in PH. CONCLUSIONS: Pediatric PH patients demonstrate reduced LV strain/strain rate, predominantly within the septum, with relationships to invasive hemodynamics, RV strain, and functional PH measures.